Victimisation of Women in Select Partition Narratives of Saadat Hasan Manto - Hariom Rawat Prof. Mudita Agnihotri (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The history of the Partition of the Indian Subcontinent is the history of the birth of two nations, India and Pakistan. This was the result of the divide-and-rule policy by the British colonial administration. Partition Literature deals with the theme of displacement, loss, pain, and suffering of those who were part of the mass migration in 1947 due to the political unrest. During the process of Partition, there was unimaginable violence across the country. Millions of people migrated during this time, and other religious groups extensively targeted women and children. Thousands of women were abducted, raped, and burnt to hurt other religions' sentiments. During the exchange of the people, they faced brutal violence by their respective religious groups. Mainly, the victims of this migration were women and children. The marginalisation of women can be seen in the select short stories of Saadat Hasan Manto. During Partition, in the name of family honour, many women were forced to commit suicide. If a woman was abducted, they were outcasted by their family for losing their innocence. Many women were publicly humiliated and even had their genitalia mutilated. Women were merely objectified and exploited by the patriarchal mainstream society, where their voices were suppressed.